TALKSHOW PERGAULAN BEBAS DAN KENAKALAN REMAJA PADA SISWA/I KELAS 9 DI MTS PSM DESA JELI - Firstalenda Susgaleni; Aufa, Kafa Billah; Ahmad Umar Wira Hadi Kusuma; Siti Lutfiyatul Aini; Zulfa Sya’banir Rahma; Azizah Permatasari; Isnada Zulfa (P3M STAI KH. MUHAMMAD ALI SHODIQ, 2025)
The Community Service Program (KKN) serve as a concrete action of student dedication to the community, one of the way to realizing that is through educational outreach. The talk show themed “Unhealthy Social Relationship and Juvenile Delinquency”, organized by KKN students from UIN Sayyid Ali Rahmatullah Tulungagung at MTS PSM Jeli, aimed to raise students’ awareness about the negative impacts of Unhealthy Social Relationship and the growing issues of juvenile delinquency. The activity was conducted using interactive approach that include presentations, discussions, also question-and-answer sessions. The outcome revealed high enthusiasm among participants and an increase in awareness about the importance of choosing healthy social circles. In conclusion, this talk show succesfully made a positive contribution in shaping more socially responsible teenage character. It is hoped that this program can be continued and developed by schools and the community as part of preventive efforts against deviant behavior among teenagers. Keywords: KKN, Unhealthy Social Relationships, Juvenile Deliquency, Education